Construction and Evaluation of a Subcutaneous Splenic Injection Port for Serial Intraportal Vein Cell Delivery in Murine Disease Models - Toshio Miki; Chika Takano; Irving M. Garcia; Brendan H. Grubbs (Stem Cells International)
The liver is the largest internal organ and the center of homeostatic metabolism. Liver-directed cell transplantation is, therefore, an attractive therapeutic option to treat various metabolic disorders as well as liver diseases. Although clinical liver-directed cell transplantation requires multiple cell injections into the portal venous system, a mouse model is lacking which allows us to perform repetitive cell injections into the portal venous system. Here, we propose a surgical model that utilizes the spleen as a subcutaneous injection port. Mouse spleens were translocated under the skin with intact vascular pedicles. Human placental stem cell transplantations were performed one week following this port construction and repeated three times. Cell distribution was analyzed by quantifying human DNA using human Alu-specific primers. About 50% of the transplanted cells were located homogeneously in the liver one hour after the splenic port injection. Fluorescent-labeled cell tracking and antihuman mitochondrion immunohistochemistry studies demonstrated that the cells localized predominantly in small distal portal branches. A similar cell distribution was observed after multiple cell injections. These data confirm that the subcutaneous splenic injection port is suitable for performing repetitive cell transplantation into the portal venous system of mouse models.